A conceptual model of the distinctive behavior of a personality - GAVAZA, Lesya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . Modern society is characterized by a variety of individual characteristics manifested in a person's behavior. Distinctiveness is a type of behavior described by non-stereotypical actions, a person's tendency to manifest individuality, and the desire to be socially visible, aiming to create an impression and gain the attention of others. Objective. To develop and disclose a conceptual model of the distinctive behavior of personality.M e t h o d s . Euler-Venn diagrams were used to graphically represent the relationship between distinctive behavior and norms in a particular subject area.R e s u l t s . Two functional dependencies for social and personal factors influencing distinctive behavior are proposed. The concept of "norms", defined from the "angle of view" of the subject area in which a particular norm was formed, is introduced. Two functional dependencies for social and personal factors influencing distinctive behavior are formulated. The concept of norms defined from the "angle of view" of the subject area R is introduced. At the social system level, the forms of distinctiveness manifestation are hypothetically divided. The theory of optimal distinctiveness is considered. The proposed classification of behavioral signs of individual distinctiveness as an element of the social system is divided into three groups, and the main components of each group are highlighted.C o n c l u s i o n s . Through theoretical analysis of the scientific literature, it was determined that distinctive behavior can be described as a type of personality behavior based on the desire to express identity while overcoming the social norms that have developed in a certain reference group in the current period.
Keywords: distinctiveness; model of distinctive behavior; behavioral manifestations of distinctive behavior; identity; individuality; difference